Challenges and reflections on teacher training in times of Covid-19:an analysis from educational psychology (2021)
Objective: to analyze the pedagogical practice experiences of teachers in training during the COVID-19 contingency, making visible the challenges, conditions, and emerging reflections of the pedagogical practice in pandemic and social isolation and characterize the teaching-learning strategies that favor skills in teachers’ profes-sional practices consistent with the need for mental health care and maintenance of the quality of life of students. Materials and methods: this research was developed from the constructivist paradigm and through the methodology of systematization of experiences. The study sample consisted of 231 students from strata 1, 2, and 3, and 11 practice advisers from a professional teacher training program. Results: pro-fessional practices in teacher training are a crucial moment for the development and strengthening of competencies associated with teaching-learning from the discipline. Before 2020, most of the professional practices were developed in-person, a situation that changed in the health contingency of COVID-19, causing a demand for sudden adaptation on the part of trainers and teachers in training for the development of practices professionals in virtual environments. Conclusions: at the end of the study, the different emerging challenges are evidenced, such as a weak command of information and communication technologies, empathy as a cognitive-emotional teacher compe-tence, the constant maintenance of student motivation and the application of curricular flexibility strategies. Likewise, prevention and support actions developed based on an adaptive educational environment are identified, which favors successful training in times of social distancing, quarantine and isolation.Keywords: psychology;professional practice; education; coronavirus infections; higher education